Corporate governance and elites - Nakpodia, Franklin; Adegbite, Emmanuel (Elsevier, 2018)
Using a qualitative methodology (interviews), we examine the relationship between the effectiveness of corporate governance mechanisms and elitist interventions. In doing this, we identify three elitist groups – political, cultural and religious, and investigate how they shape the legitimacy and effectiveness (or otherwise) of the institutional drivers of corporate governance in Nigeria. We caution the widely-held notion in the literature which suggests that institutions act as a check on the behaviour of elites and influence how elites compete and emerge. Alternatively, we argue that elites, in the presence of institutional voids, can invent, circumvent and corrupt institutions.